The novel GlcNAc 6-phosphate dehydratase NagS governs a metabolic checkpoint that controls nutrient signaling in Streptomyces - Li, Chao; Urem, Mia; Kotsogianni, Ioli; Lau, Josephine; Du, Chao; Elsayed, Somayah S.; Martin, Nathaniel I.; McNae, Iain W.; Voskamp, Patrick; Mayer, Christoph; Rigali, Sébastien; Pannu, Navraj; et al. (PLOS Biology, 2025)
N-acetylglucosamine (GlcNAc) accumulation acts as a key metabolic signal in Streptomyces, but how it triggers developmental responses is unclear. This study shows that the novel enzyme NagS dehydrates GlcNAc-6P into a reactive intermediate, triggering a toxicity-based checkpoint that governs nutrient signalling in Streptomyces.